Suppose you have the expression as:
isn't it that the law of exponent states that
then that makes the expression
isn't it that when you divide x² by x² directly you'll get 1?
now let's have this sequence
2³ = 8
2² = 4
did you notice that when you subtract the exponent from cube to square(3-1), it's just 8/2=4? it's the same thing happened when you have exponents 1 and 0 from exponent 1 2^1 = 2 since you are to get the value for the number raised to zero then all you have to do is divide 2 by 2 = 1